Milícia, grupos policiais, tráfico de drogas e território: Uma análise localizada em Uberlândia/MG - Gomes, Laura Bianca Rodrigues (2023)
This work aims to analyze metanarratives that denounce the presence of militia groups in the city of Uberlândia. Thus, from the emergence of exposures by the judiciary of the existence of these groups in the city, we started the research with the guiding hypothesis that different spaces and narratives mobilized this term for criminal actions in the city. However, since the concept is linked to the reality of Rio, what are the similarities and differences present in these groups in the city and how this affects community life. The research encountered several challenges and institutional, health limits, since most of the research was carried out during the COVID-19 pandemic and the theme deals with delicate subjects, however, it was still possible to contact, experience and talk with people, professionals and social actors fundamental policies for its development. To better work the research dilemmas, we used the perspective of active ethnography based on the methodology of researcher Veena Das. It is concluded that although several groups articulate the concept of militia to say about the actions of some police officers who act in a punctual way in corruption schemes that involve more economic gains. However, throughout the research it was possible to understand a little of the crime-business that the Primeiro Comando da Capital undertakes on the outskirts of Uberlândia.